Stress dan Perilaku Agresi Pada Ibu Rumah Tangga yang Tidak Bekerja di Surabaya - Aristawati, Akta Ririn (Persona:Jurnal Psikologi Indonesia, 2016)
The purpose of this research was to know a significant correlation between the level of stress with the level of aggresive behaviour in unemployed housewives. This research is a correlation research. The population of this research were the unemployed housewives in Surabaya, with 100 person as the sample. The sampling technique used purposive sampling, that was a selection technique of the subject by using certain consideration. The collecting data method was questionnaire to expose the level of stress and the level of aggresive behaviour in unemployed housewives. The data analysis used Chi-Square (Ï‡ 2) analysis. After analyzed by the Chi-Square analysis (Ï‡ 2) obtained the correlation coefficient of 0.526 with a significance value of 0.000 (p<0.01) which means that there is a significant correlation between the level of stress with the level of aggresive behaviour in unemployed housewives. Thus, the hypotesis proposed in this research that â€œthere is a significant correlation between the level of stress with the level of aggresive behaviour in unemployed housewivesâ€ was accepted. So if can be conclused that there were a positive and significant correlation between the level of stres and the level of aggresive behaviour in unemployed housewives .Keywords : Stress, Aggressive behaviour, unemployed housewives